2010
DOI: 10.1177/0016986209355974
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Psychosocial Characteristics of Gifted Students With Written Language Disability

Abstract: Gifted and talented students who also have a specific learning disability (SLD) are typically referred to as twice-exceptional and are among the most underserved students in our schools. Previous special education laws promoted a wait-to-fail approach; therefore, gifted students with SLD often were overlooked because their average academic performance was not “failure” enough. The flip side to this was the fact that students’ giftedness, as measured by general ability tests, often was masked by average, yet re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
144
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(160 citation statements)
references
References 18 publications
7
144
0
3
Order By: Relevance
“…Waldron and Saphire (1990) also established through the comparison of WISC-R sub-test scores of students who were gifted and students who were gifted with a learning disability that "there is no evidence that rank ordering of WISC-R subtests is an effective method of identifying the existence of a learning disability" (p. 497). Assouline, Foley Nicpon and Whitman (2010) noted that students who are gifted with a learning disability have a wide range of score variability supporting that it is difficult to establish a specific profile for identification of these students. Maker and Udall (1997) suggested that a wide variety of information is required in order to identify students who are gifted and learning disabled.…”
mentioning
confidence: 99%
“…Waldron and Saphire (1990) also established through the comparison of WISC-R sub-test scores of students who were gifted and students who were gifted with a learning disability that "there is no evidence that rank ordering of WISC-R subtests is an effective method of identifying the existence of a learning disability" (p. 497). Assouline, Foley Nicpon and Whitman (2010) noted that students who are gifted with a learning disability have a wide range of score variability supporting that it is difficult to establish a specific profile for identification of these students. Maker and Udall (1997) suggested that a wide variety of information is required in order to identify students who are gifted and learning disabled.…”
mentioning
confidence: 99%
“…And, above all, an analysis between ability and achievement is crucial in clarifying whether learning disability or learning style is the reason for gifted students' academic struggles. It is very important to have a syllabus or program or activity which guides teachers in identifying students who do possess high verbal abilities but might be hidden due to disability (Assouline et al, 2010). Therefore, it is also vital for all authorities to address the issue of whether or not the students really are academically gifted; whether or not these students have a learning disability; and whether or not a particular gifted program applies the right pedagogical approach.…”
Section: Resultsmentioning
confidence: 99%
“…And it was proven by the result of this study that the subjects scored higher on communication apprehension. Assouline et al (2010) explained in a study that gifted students' verbal abilities were extremely well-developed and advanced than their non-verbal abilities eventhough they were diagnosed with a disability that is verbally-based. They further elaborated that eventhough the gifted students' verbal and non-verbal abilities were generally above their age-level expectations, however, their working memory and processing speed abilities were similar to normal children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations